Third-party electric vehicle battery remanufacturing supply chains - Fadwa Dababneh; Hussam Zuhair Aldababneh; Yiran Yang (Cleaner Logistics and Supply Chain)
Currently, battery manufacturers face many challenges keeping up with the growing demand for electric vehicle (EV) batteries. This high demand comes from two main sources: growing battery demand for newly manufactured EVs and battery replacement demand for already-on-the-road EVs. Circularity through different end-of-life strategies can help alleviate the current electric EV battery supply and demand gap while tackling accumulating waste challenges. In particular, remanufacturing has shown to be a promising value recovery strategy for spent EV batteries to be reused for automotive applications affordably and sustainably. Hence, a mathematical model is developed to study an independent remanufacturing (IR) supply chain for EV battery replacement demand intended for already on-the-road EVs. The model considers remanufacturers’ self-sufficiency, incoming spent battery quality levels, and rush orders. Using the developed model, a numerical case study, based on data for California, is implemented. The case study results suggest that remanufacturing EV batteries to meet the demand for already on-the-road EVs is profitable and incorporating rush order deliveries could be economically viable. Furthermore, while both self-sufficient and non-self-sufficient remanufacturing configurations have shown to be economically viable, both have tradeoffs that must be considered.